Cape Basin, seismic profile AWI-96008 - Gabriele Uenzelmann-Neben; Estella Weigelt (PANGAEA, 2023)
Processed data (SEGY) of seismic reflection profile AWI-96008 collected during RV Meteor cruise M34/1 in 1996. Migrated data collected with 600 m analogue streamer, 1 GI-guns was used as seismic source every 25 m. See cruise report of M34/1 and readme file 96008_segd_info for further details on acquisition parameters.